Gastric Perforation After a Dog Attack. Issue 1 (January 2018) - Uchino, Hayaki; Kuriyama, Akira; Bruce, John; Laing, Grant; Clarke, Damian; Oosthuizen, George
Abstract : Abstract: Dog bites are a major cause of injury, especially in the pediatric population. Common anatomic sites of dog bites on children are the peripheries and the head and neck. The torso is reportedly injured less frequently, and only 2 cases of intra-abdominal injury secondary to dog bites have been reported. We recently encountered a 3-year-old boy presenting with peritonitis who had sustained multiple dog bites to his trunk and upper limbs. Emergency laparotomy was performed. Surgical findings revealed penetration of the peritoneum and single perforation of the anterior gastric wall with multiple tooth marks; thus, the gastric perforation was debrided and repaired. After receiving rabies prophylaxis and amoxicillin-clavulanate, the patient had an uneventful postoperative course. The principles of management of dog bites include debridement of wounds and use of prophylactic antibiotics. Because rabies is always fatal, postexposure prophylaxis should be considered in appropriate cases. Dog bites can be life-threatening, and prevention is the best approach to solve this problem. Clinicians need to be aware that some dog bites can be devastating and should be familiar with the principles of managing these wounds.